ANALYSIS OF THE EFFECTIVENESS OF CANVA MULTIMEDIA ON THE COGNITIVE ABILITIES AND LEARNING MOTIVATION OF ELEMENTARY SCHOOL STUDENTS IN GRADE V (PIONIR: JURNAL PENDIDIKAN, 2025)
This study aims to explore the effectiveness and contextual factors influencing the use of Canva-based interactive learning multimedia in enhancing the cognitive abilities and learning motivation of fifth grade elementary school students. A qualitative descriptive literature review design was employed, chosen to provide a comprehensive understanding of patterns, mechanisms, and perceptions across prior studies rather than to measure quantitative outcomes. Ten peer reviewed articles published between 2020 and 2025 were examined. Data extracted from these studies included research objectives, participants, educational contexts, methodological approaches, and emerging themes. The analysis was conducted through narrative and thematic synthesis to identify consistent findings and variations across the literature. The results revealed that Canva-based media fostered student engagement, improved visualization of learning materials, and positively influenced both learning outcomes and motivation. Despite challenges such as limited facilities and varying teacher competencies, professional training and institutional support effectively addressed these barriers. Thus, Canva is recognized as a relevant and applicable digital learning tool supporting character- and technology-oriented education within the Independent Curriculum framework.Keywords: Multimedia, cognitive ability, learning motivation
Keywords: Multimedia; cognitive ability; learning motivation.